Education for Education...Or for Skills? - Hanushek, Eric A. (2012)
Countries in the developing world were led to believe that education would put them on the path to becoming modern economiesand they responded enthusiastically. Education for All was a powerful message that has led to a veritable transformation of schooling throughout the world.